2006
DOI: 10.1007/s11095-006-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surfactant on PLGA Microsphere Glass Transition and Water Sorption: Remodeling the Surface Morphology to Attenuate the Burst Release

Abstract: These studies suggested that the mechanical stability of PLGA was influenced by the addition of surfactants, which, depending on the formulation, led to surface pore remodeling under high humidity, reducing the initial burst release while maintaining the spherical integrity of the microsphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 51 publications
9
52
0
Order By: Relevance
“…The thermogram of PLGA shown in Fig. 5b reveals a glass transition temperature around 35-37°C which is in agreement with literature (25). The thermogram of physical mixtures of CPX and PLGA (weight ratio of 1:3) exhibited a glass transition which can be ascribed to PLGA and an exothermic peak due decomposition of CPX.…”
Section: Thermal Behavior Of the Microspheressupporting
confidence: 88%
See 1 more Smart Citation
“…The thermogram of PLGA shown in Fig. 5b reveals a glass transition temperature around 35-37°C which is in agreement with literature (25). The thermogram of physical mixtures of CPX and PLGA (weight ratio of 1:3) exhibited a glass transition which can be ascribed to PLGA and an exothermic peak due decomposition of CPX.…”
Section: Thermal Behavior Of the Microspheressupporting
confidence: 88%
“…The obtained microspheres had a spherical shape and smooth surface, with some small pores. These pores can be attributed to the migration of inner aqueous droplets to the microsphere surface during emulsification (25).…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…This can be partially attributed to the difference in hydrophobicity of the microspheres due to the different surfactant blends. The hydration of the particles was strongly influenced by the hydrophilicity of the surfactants, which enhances the degradation rate of the particles leading to faster release [2]. F4, which was relatively more hydrophobic than F6 and also had larger particle size, exhibited faster release with a very high burst release.…”
Section: Discussionmentioning
confidence: 99%
“…The technique requires surfactant as the main component in the fabrication. A number of studies employing the technique have shown that surfactants had effects on the particle physical aging [2], internal structure [3] and morphological characteristics, [4].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation technique can vary depending on the application of the PLGA vehicles (Bouissou et al, 2006;Chaisri et al, 2009;Rosca et al, 2004). In the present work, PLGA (50:50) microspheres (3-0.5 m) have been prepared by double emulsion method.…”
Section: Plga -Particlesmentioning
confidence: 99%